Estimating returns to fertilizer adoption with unobserved heterogeneity: evidence from Ethiopia - Assfaw Wossen, Tesfamicheal; Gatiso, T.T.; Kassie, M. (Wiley, 2018)
This paper examines the relationship between chemical fertilizer adoption and agricultural productivity in Ethiopia. Our results suggest that average returns to fertilizer adoption are high. Further, we find substantial heterogeneity across farm households in returns to fertilizer adoption, with comparative advantage playing a significant role in the adoption decision of farmers. While the adoption decision of farmers was largely rational, fertilizer use across plots was sub‐optimal. The results of this paper underscore the importance of improving farmers awareness about proper use of fertilizer through site‐specific extension services for improving agricultural productivity.